Strategies for Developing Fine Motor Skills in Early Childhood at PAUD Harsya Ceria - Alfina Alfina; Rani Puspa Juwita (Fakultas Keguruan dan Ilmu Pendidikan, 2026)
This study aims to describe the strategies used by teachers in developing fine motor skills of early childhood learners at PAUD Harsya Ceria. The research employed a descriptive qualitative approach with data collection techniques consisting of observation, interviews, and documentation. The research subjects included teachers and early childhood learners who participated in fine motor learning activities. The results indicate that teachers implemented well-planned strategies through opening activities, core activities, reflection, and closing sessions. During the core activities, teachers employed various tasks such as drawing, coloring, cutting, pasting, threading, as well as life skills activities including opening and closing bottles and buttoning clothes. These strategies were tailored to the individual abilities of children, including children with special needs, ensuring that each child received equal learning opportunities. Teachers also integrated play-based approaches, demonstrations, direct assistance, and scaffolding to help children coordinate finger and hand movements. Evaluation was conducted through observation and assessment of children’s work. Overall, the implemented strategies proved effective in improving fine muscle strength, hand–eye coordination, concentration, and children’s independence. These findings emphasize the importance of varied and adaptive learning planning in optimizing the development of fine motor skills in early childhood.